High specific capacitance isomelanin nanomaterial and electrode sheet and preparation method thereof
By oxidizing and aggregating 1,8-dihydroxylhine at normal temperature, synthesize and activate heteroglobin, the existing carbon-based supercapacitors have limited problems than capacitors. Materials, with good industrialization prospects.
Patent Information
- Application Number
- CN202211650209.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The limited specific capacitance and cumbersome manufacturing process of existing carbon-based supercapacitors hinder their wide commercial applications.
By analyzing the structural analysis of natural melanin, starting from 1,8-dihydroxylhine, a pot of oxidation polymerization at room temperature is used at room temperature to synthesize different melanin, and the geothermal treatment and KOH activation processing is prepared to prepare high-ratio capacitors with high ratio capacitors. Bigbin -in -area is different melanin nanomaterials.
The preparation of alien nano -materials for high -ratio capacitors has been realized. The ratio of the material is greater than 1900m2/g, and the preparation method is simple, repetitive, and has a good industrialization prospect.
Smart Images

Figure CN116053053B_ABST
Abstract
Description
Technical Field
[0001] The present invention provides an isomelanin nanomaterial and an electrode sheet with high specific capacitance and a preparation method thereof. Specifically, it relates to an isomelanin nanomaterial and a nanoelectrode sheet with large specific surface area and a preparation method thereof, belonging to the technical field of melanin application. Background Art
[0002] Carbon-based supercapacitors are high-performance energy storage devices with high capacity and ultra-long cycle life, and are one of the key enabling technologies for the future of new energy. However, limited specific capacitance and cumbersome manufacturing processes have hindered the widespread commercial application of carbon-based supercapacitors. Currently established methods for preparing high-performance carbon-based electrode materials include: 1. Screening and preparation of high-capacitance original carbon matrices; 2. Heteroatom doping and metal oxide / metal sulfide loading in carbon matrices; 3. Rational design and efficient construction of hierarchical porous structures. Although many preparation methods for carbon-based materials have been reported, the further development of high-performance carbon-based supercapacitors has been severely hindered by the lack of sufficient original carbon matrices and easy pore-forming strategies. Therefore, the continuous exploration of new original carbon matrices with hierarchical porous structures and high specific surface area values is the eternal pursuit of preparing high-performance carbon-based supercapacitors.
[0003] Melanin is a class of dark insoluble pigments widely found in nature, and has attracted extensive attention in fields such as biomedicine and energy applications. According to the definition, natural melanin can be divided into five major categories: eumelanin, pheomelanin, neuromelanin, isomelanin and pyomelanin. Melanin shows hydration-dependent mixed ion-electronic conductivity, and the polycatechol structure exhibits a variety of catechol-quinone redox functional groups. At the same time, recent progress has also shown that a large number of N and S heteroatoms in melanin can improve the overall electrochemical activity and promote Faradaic processes. In addition, the carbonization of melanin can further generate a graphite-like ordered layered microstructure with hierarchical pores and an extensive cross-linked network, which is conducive to the storage and rapid transport of electrolyte ions. All these characteristics make melanin one of the most promising biomacromolecule candidates for further design and fabrication of supercapacitor electrode materials.
[0004] Isomelanin is a melanin found in fungi and composed of the nitrogen-free precursor 1,8-dihydroxybenzene (1,8-DHN). Studies have shown that fungi containing isomelanin have stronger radiation resistance based on its strong antioxidant properties and energy conversion behavior. Notably, the chemical structure of oligomers and polymers derived from 1,8-DHN shows that the material has inherent microporosity, which is conducive to the construction of porous graphitic carbon with a large specific surface area. In addition, during the chemical activation process, the o-naphthol group of 1,8-DHN can also promote the generation of electrochemically active oxygen functionalization. Summary of the invention
[0005] The purpose of the present invention is to provide an isomelanin nanomaterial with a large specific surface area and high specific capacitance, an electrode and a preparation method thereof. The present invention analyzes the structure of natural isomelanin, starts from the precursor molecule 1,8-dihydroxynaphthalene of isomelanin, synthesizes isomelanin by a one-pot oxidative polymerization at room temperature, and obtains an isomelanin nanomaterial with a large specific surface area and high specific capacitance by further heat treatment and KOH activation treatment.
[0006] In one aspect, the present invention provides a method for preparing an isomelanin nanomaterial, comprising the following steps:
[0007] S1 Preparation of 1,8-dihydroxynaphthalene solution
[0008] Specifically, 1,8-dihydroxynaphthalene is dissolved in a mixed solvent of acetone and water, and stirred at room temperature to fully mix the mixture to obtain a uniform 1,8-dihydroxynaphthalene solution;
[0009] Wherein, in the mixed solvent, the volume fraction of acetone is 5-25%, preferably 10%, and the volume fraction of water is 75-95%, preferably 90%;
[0010] The content of 1,8-dihydroxynaphthalene in the 1,8-dihydroxynaphthalene solution is 0.5-3 mg / mL, preferably 2 mg / mL;
[0011] S2 Preparation of 1,8-dihydroxynaphthalene-iron ion complex solution
[0012] Specifically, slowly add an aqueous solution of iron trichloride hexahydrate to the 1,8-dihydroxynaphthalene solution of S1 and stir for 5 minutes to obtain a dark gray 1,8-dihydroxynaphthalene-iron ion complex solution;
[0013] Wherein, the concentration of the aqueous solution of ferric chloride hexahydrate is 1 mol / L;
[0014] The amount of the aqueous solution of ferric chloride hexahydrate added is calculated based on the mass ratio of 1,8-dihydroxynaphthalene to ferric chloride hexahydrate in a range of 1:0.5-1:1;
[0015] S3 slowly adds potassium dichromate aqueous solution to the 1,8-dihydroxynaphthalene-iron ion complex solution of S2 to react and obtain a black solution;
[0016] Specifically, slowly add potassium dichromate aqueous solution to the 1,8-dihydroxynaphthalene solution of S1, and stir the reaction at room temperature for 4-48 hours to obtain a black reaction solution;
[0017] Wherein, the concentration of potassium dichromate aqueous solution is 100 mg / mL;
[0018] The amount of potassium dichromate solution added is based on a mass ratio of 1,8-dihydroxynaphthalene to potassium dichromate of 1:0.5-1:1, preferably 1:0.7
[0019] Wherein, the stirring time is 4-48h, preferably 20h;
[0020] S4 centrifuges, washes, and dries the black solution obtained in S3 to obtain isomelanin nanomaterials;
[0021] The centrifugal speed is 12000-16000 r / min, the centrifugal time is 5-10 min, and the washing is three times of deionized water washing;
[0022] S5 treats the isomelanin nanomaterial of S4 at high temperature under an inert atmosphere to obtain the isomelanin nanomaterial;
[0023] Specifically, the isomelanin nanomaterial obtained in S4 is placed in an inert gas atmosphere (nitrogen or argon) and heated to a heat treatment temperature of 500°C-1000°C, preferably 600°C, at a heating rate of 2-10°C / min, and heat treated for 1-4 hours, preferably 2 hours, and then cooled to room temperature at a cooling rate of 2-10°C / min to obtain the isomelanin nanomaterial.
[0024] S6 grinds and blends the isomelanin nanomaterial of S5 with KOH, and performs high-temperature treatment under an inert atmosphere to obtain a black mixed material.
[0025] Specifically, the isomelanin nanomaterial obtained in S5 is ground and blended with KOH, the mass ratio of isomelanin nanomaterial to KOH is 1:1-1:20, preferably 1:4, and then in an inert gas atmosphere (nitrogen or argon), the temperature is raised to a heat treatment temperature of 500°C-1000°C, preferably 600°C, at a heating rate of 2-10°C / min, and the heat treatment is performed for 1-4 hours, preferably 2h, and then the temperature is returned to room temperature at a cooling rate of 2-10°C / min to obtain a black mixed material.
[0026] S7 washes the black mixed material of S6 with dilute hydrochloric acid and water, centrifuges, and dries to obtain isomelanin nanomaterials with a large specific surface area.
[0027] The centrifugal speed is 12000-16000 r / min, the centrifugal time is 5-10 min, and the washing is performed three times with dilute hydrochloric acid and deionized water respectively, and the hydrochloric acid concentration is 1M.
[0028] On the other hand, the present invention provides an isomelanin nanomaterial, which is prepared by the aforementioned method for preparing an isomelanin nanomaterial electrode.
[0029] Furthermore, the specific surface area of the isomelanin nanomaterial of the present invention is greater than 1900 m 2 / g.
[0030] On the other hand, the present invention provides an application of an isomelanin nanomaterial as an electrode material for a supercapacitor, and provides an isomelanin nanopole sheet. The aforementioned isomelanin nanomaterial is mixed with carbon black and polytetrafluoroethylene, and ultrasonically dispersed in an aqueous solution, and then dried at 80°C to obtain a black substance. After folding and rolling, an isomelanin-based carbon nanofilm with a large specific surface area and adjustable thickness is obtained, which is then pressed with a current collector (nickel foam, foam barrel, aluminum foil, copper foil or stainless steel) at 0.5-50MPa to obtain an electrode sheet.
[0031] The mass ratio of polytetrafluoroethylene to the isomelanin-based carbon nanomaterial with a large specific surface area is 1:5-1:20, preferably 1:8.
[0032] Wherein, the mass ratio of polytetrafluoroethylene to carbon black is 1:0.2-1:5, preferably 1:1.
[0033] The present invention achieves the following technical effects through the above technical scheme.
[0034] The precursor molecule 1,8-dihydroxynaphthalene and the oxidant potassium dichromate used in the synthesis process of the preparation method of the isomelanin nanomaterial of the present invention are both common reagents with standard production specifications, which are very convenient to use and make this method have good repeatability.
[0035] The method used in the preparation of the isomelanin nanomaterial of the present invention is very simple. In addition to the precursor molecules and the oxidant, only two relatively green and environmentally friendly solvents, water and acetone, are used, avoiding the introduction of a large amount of other organic solvents, thereby ensuring the green, environmentally friendly and safe characteristics of the entire process.
[0036] The preparation method of the isomelanin nanomaterial adopted in the present invention uses oxidative polymerization at room temperature as the reaction method, and isomelanin is artificially synthesized simply through a one-pot method.
[0037] The preparation method of the isomelanin nanomaterial adopted in the present invention is highly efficient, repeatable, and scalable, has good industrialization prospects, and has great advantages in practical applications.
[0038] The preparation method of the isomelanin nanomaterial provided by the present invention has good adjustability, and the morphology and structure of isomelanin nanoparticles can be regulated by adjusting the reaction time, reactant concentration, oxidant type, solvent ratio, heat treatment temperature, and the mass ratio of KOH to carbon material.
[0039] The preparation method of the isomelanin nanomaterial provided by the present invention first synthesizes a metal-naphthol complex and then polymerizes it, which can achieve a higher metal loading, and then carbonizes it. During the carbonization process, since the carbon element has a reducing effect at high temperature, the carried metal ions can be reduced to nano-metals. Without adding additional preparation steps, uniform and efficient composite of nano-metals can be achieved, thereby providing a higher specific capacitance.
[0040] The preparation method of the isomelanin electrode sheet provided by the present invention is simple, efficient and has good adjustability. A material with excellent secondary processability can be obtained by compounding and drying simple components, and the thickness and size of the prepared film can be easily customized.
[0041] The isomelanin nanomaterial with a large specific surface area provided by the present invention has a high specific surface area, a developed pore structure, and a high specific capacitance. -1 407F g can be achieved at a current density of -1 High specific capacitance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope image of the isomelanin nanomaterial of Example 1 of the present invention;
[0043] Figure 2 This is a specific surface area diagram of the isomelanin nanomaterial of Example 1 of the present invention;
[0044] Figure 3 This is the BET pore size distribution diagram of Example 1 of the present invention;
[0045] Figure 4 Specific capacitance diagram of the isomelanin nanomaterial of Example 1 of the present invention at different current densities;
[0046] Figure 5 Specific capacitance diagrams of the isomelanin nanomaterials of Example 1 and Examples 1-8 to 1-10 of the present invention at different current densities;
[0047] Figure 6 Specific capacitance diagrams of the isomelanin nanomaterials of Example 1 and Examples 1-11 to 1-13 of the present invention at different current densities;
[0048] Figure 7 The metal ion content statistical graph of Example 1 of the present invention and the metal-naphthol nanoparticles doped with the same mass of ferric chloride hexahydrate obtained by first oxidizing and polymerizing isomelanin nanoparticles prepared by the same chemical method as a control;
[0049] Figure 8The present invention is Example 1 and the metal-naphthol nanoparticles doped with the same amount of ferric chloride hexahydrate are prepared by first oxidizing and polymerizing isomelanin nanoparticles and then adding the same amount of ferric chloride hexahydrate as the control. -1 Plot of specific capacitance at different current densities. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0051] The present invention adopts an oxidative polymerization method, with potassium dichromate as an oxidant, 1,8-dihydroxynaphthalene as a precursor small molecule for the reaction, acetone and water as a mixed solvent, and a one-pot polymerization at room temperature to obtain isomelanin nanoparticles with uniform morphology and stable yield. Such isomelanin nanoparticles have a chemical structure and properties similar to those of natural isomelanin. Furthermore, the prepared isomelanin nanoparticles are constructed by oligomer self-assembly, naturally have a certain microporosity, and have a high specific surface area after carbonization and KOH activation. Furthermore, an isomelanin electrode sheet capable of obtaining a high specific capacitance is obtained by an efficient processing method.
[0052] The present invention provides a method for preparing an isomelanin nanomaterial with a large specific surface area, comprising the following steps:
[0053] S1 Preparation of 1,8-dihydroxynaphthalene solution
[0054] Specifically, 1,8-dihydroxynaphthalene is dissolved in a mixed solvent of acetone and water, and stirred at room temperature to fully mix the mixture to obtain a uniform 1,8-dihydroxynaphthalene solution.
[0055] Wherein, in the mixed solvent, the volume fraction of acetone is 5-25%, preferably 10%, and the volume fraction of water is 75-95%, preferably 90%;
[0056] The content of 1,8-dihydroxynaphthalene in the 1,8-dihydroxynaphthalene solution is 0.5-3 mg / mL, preferably 2 mg / mL;
[0057] S2 Preparation of 1,8-dihydroxynaphthalene-iron ion complex solution
[0058] Specifically, an aqueous solution of iron trichloride hexahydrate is slowly added to the 1,8-dihydroxynaphthalene solution of S1, and the mixture is stirred for 5 minutes to obtain a dark grey 1,8-dihydroxynaphthalene-iron ion complex solution.
[0059] Wherein, the concentration of the aqueous solution of ferric chloride hexahydrate is 1 mol / L;
[0060] Wherein, the amount of the aqueous solution of iron trichloride hexahydrate added is calculated based on the mass ratio of 1,8-dihydroxynaphthalene to iron trichloride hexahydrate of 1:0.2-1:0.7, preferably 1:0.5;
[0061] Wherein, the concentration of the aqueous solution of ferric chloride hexahydrate is 1 mol / L;
[0062] Wherein, the amount of the aqueous solution of iron trichloride hexahydrate added is such that the mass ratio of 1,8-dihydroxynaphthalene to iron trichloride hexahydrate is 1:0.5-1:1;
[0063] Among them, the stirring time is 5min;
[0064] S3 slowly adds potassium dichromate aqueous solution to the 1,8-dihydroxynaphthalene solution of S2 to obtain a black solution;
[0065] Specifically, slowly add potassium dichromate aqueous solution to the 1,8-dihydroxynaphthalene-iron ion complex solution of S2, and stir the reaction at room temperature for 4-48 hours to obtain a black reaction solution;
[0066] Wherein, the concentration of potassium dichromate aqueous solution is 100 mg / mL;
[0067] The amount of potassium dichromate solution added is based on a mass ratio of 1,8-dihydroxynaphthalene to potassium dichromate of 1:0.5-1:1, preferably 1:0.7;
[0068] Wherein, the stirring time is 4-48h, preferably 20h;
[0069] S4 centrifuges, washes, and dries the black solution obtained in S3 to obtain isomelanin nanomaterials;
[0070] The centrifugal speed is 12000-16000 r / min, the centrifugal time is 5-10 min, and the washing is three times of deionized water washing;
[0071] S5 treats the isomelanin nanomaterial of S4 at high temperature under an inert atmosphere to obtain the isomelanin nanomaterial.
[0072] Specifically, the isomelanin nanomaterial obtained in S3 is placed in an inert gas atmosphere (nitrogen or argon) and heated to a heat treatment temperature of 500°C-1000°C, preferably 600-800°C, more preferably 600°C, at a heating rate of 2-10°C / min, for 1-4 hours, preferably 2 hours, and then cooled to room temperature at a cooling rate of 2-10°C / min to obtain the isomelanin nanomaterial.
[0073] S6 grinds and blends the isomelanin nanomaterial of S5 with KOH, and performs high-temperature treatment under an inert atmosphere to obtain a black mixed material.
[0074] Specifically, the isomelanin nanomaterial obtained in S4 is ground and blended with KOH, the mass ratio of isomelanin nanomaterial to KOH is 1:1-1:20, preferably 1:4, and then in an inert gas atmosphere (nitrogen or argon), the temperature is raised to a heat treatment temperature of 500°C-1000°C, preferably 600-800°C, more preferably 600°C, at a heating rate of 2-10°C / min, and the heat treatment is performed for 1-4 hours, preferably 2h, and then the temperature is returned to room temperature at a cooling rate of 2-10°C / min to obtain a black mixed material.
[0075] S7 washes the black mixed material of S6 with dilute hydrochloric acid and water, centrifuges, and dries to obtain isomelanin nanomaterials with a large specific surface area.
[0076] The centrifugal speed is 12000-16000 r / min, the centrifugal time is 5-10 min, and the washing is performed three times with dilute hydrochloric acid and deionized water respectively, and the hydrochloric acid concentration is 1M.
[0077] On the other hand, the present invention provides an isomelanin nanomaterial, which is prepared by the aforementioned method for preparing an isomelanin nanomaterial electrode.
[0078] Furthermore, the specific surface area of the isomelanin nanomaterial of the present invention is greater than 1900 m 2 / g.
[0079] On the other hand, the present invention provides an application of an isomelanin nanomaterial as an electrode material for a supercapacitor. The isomelanin nanomaterial is mixed with carbon black and polytetrafluoroethylene, and ultrasonically dispersed in an aqueous solution, followed by drying at 80°C to obtain a black substance, which is folded and rolled to obtain an isomelanin-based carbon nanofilm with an adjustable thickness and a large specific surface area. The film is then pressed with a current collector (nickel foam, foam barrel, aluminum foil, copper foil or stainless steel) at 0.5-50 MPa to obtain an electrode sheet.
[0080] The mass ratio of polytetrafluoroethylene to the isomelanin-based carbon nanomaterial with a large specific surface area is 1:5-1:20, preferably 1:8.
[0081] Wherein, the mass ratio of polytetrafluoroethylene to carbon black is 1:0.2-1:5, preferably 1:1.
[0082] The above are the basic ideas and implementation methods of the present invention, which will be further described below through specific examples.
[0083] Example 1
[0084] A method for preparing an isomelanin nanomaterial comprises the following steps:
[0085] S1 First, prepare a 1,8-dihydroxynaphthalene solution by dissolving 1,8-dihydroxynaphthalene in a mixed solvent of acetone and water, stirring at room temperature to fully mix the mixture to obtain a uniform 1,8-dihydroxynaphthalene solution.
[0086] Specifically, the volume fraction of acetone in the solvent is 10%, and the volume fraction of water is 90%;
[0087] The content of 1,8-dihydroxynaphthalene in the solution is 2 mg / mL;
[0088] S2 slowly added an aqueous solution of iron trichloride hexahydrate to the 1,8-dihydroxynaphthalene solution of S1 and stirred for 5 minutes to obtain a dark gray solution;
[0089] The concentration of the aqueous solution of ferric chloride hexahydrate is 1 mol / L, and the amount of the aqueous solution of ferric chloride hexahydrate added is based on a mass ratio of 1,8-dihydroxynaphthalene to ferric chloride hexahydrate of 1:0.5.
[0090] S3 slowly added potassium dichromate aqueous solution to the 1,8-dihydroxynaphthalene-iron ion complex solution of S2, and stirred the reaction at room temperature for 20 hours to obtain a black solution;
[0091] The concentration of the potassium dichromate aqueous solution is 100 mg / mL, and the amount of the potassium dichromate solution added is based on a mass ratio of 1,8-dihydroxynaphthalene to potassium dichromate of 1:0.7;
[0092] S4 centrifuges, washes, and dries the black solution obtained in S3 to obtain isomelanin nanomaterials;
[0093] The centrifugal speed was 14000 r / min, the centrifugal time was 6 min, and the washing was three times with deionized water;
[0094] S5: The isomelanin nanomaterial of S4 is heated to a heat treatment temperature of 600°C at a heating rate of 5°C / min under a nitrogen atmosphere, heat treated for 2 hours, and then returned to room temperature at a cooling rate of 5°C / min to obtain the isomelanin nanomaterial.
[0095] S6 grinds and blends the isomelanin nanomaterial of S5 with KOH, with the mass ratio of isomelanin nanomaterial to KOH being 1:4. Then, in a nitrogen gas atmosphere, the temperature is raised to a heat treatment temperature of 600°C at a heating rate of 5°C / min, heat treated for 2 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a black mixed material.
[0096] S7 washes the black mixed material of S6 with dilute hydrochloric acid and water, centrifuges, and dries to obtain isomelanin nanomaterials with a large specific surface area.
[0097] The centrifugal speed is 14000 r / min, the centrifugal time is 8 min, the washing is three times of dilute hydrochloric acid and deionized water respectively, and the hydrochloric acid concentration is 1M.
[0098] Embodiments 2 to 18 are similar to Embodiment 1, except for the relevant parameters, as shown in the following table:
[0099]
[0100]
[0101] Results Characterization
[0102] Characterization of isomelanin nanomaterials-morphology
[0103] The isomelanin nanomaterials obtained in step 2 of Examples 1 to 18 were observed under a desktop scanning electron microscope to observe the microscopic morphology of the samples obtained above.
[0104] The specific operation method is to prepare a 1 mg / mL aqueous solution of isomelanin nanoparticles, spin-coat it on the surface of a smooth mica sheet, and observe it after drying and gold spraying. Figure 1 As shown, it can be directly observed from the scanning electron microscope image that the obtained samples are all nanoparticles with good morphology and uniform distribution. After statistics, the particle size is 153-180nm.
[0105] Characterization of Isomelanopic Nanomaterials - Specific Surface Area
[0106] The sample obtained in Example 1 was subjected to an Ar isothermal adsorption-desorption curve test. Figure 2 As shown, its specific surface area is measured to be 2462.1m 2 g -1 The pore size distribution diagram is shown in Figure 3 As shown, the sample obtained in Example 1 has a rich microporous structure.
[0107] Characterization of Isomelanin Nanoparticles——Specific Capacitance Performance
[0108] In the present invention, the specific capacitance performance under different current densities is measured by an electrochemical workstation. The isomelanin nanomaterial with a large specific surface area obtained in Example 1 is used as a raw material, and constant current charge and discharge tests under different current densities are performed in a 6M KOH electrolyte. Taking the material obtained in Example 1 as an example, the change of the obtained specific capacitance with the current density is shown in FIG. Figure 4 As shown. Under the premise of maintaining 600℃ KOH activation, the electrochemical performance trend of the large specific surface area isomelanin nanoelectrode sheet with the change of heat treatment temperature can be seen in Figure 5, carbonized at 600℃, and activated with KOH at 600℃, the performance is the best. Under the condition of maintaining the first carbonization temperature at 600℃, the effect of different KOH activation temperatures on the electrochemical performance can be found in Figure 6 As shown, the performance is best when carbonized at 600°C and activated with KOH at 600°C. Referring to Example 1, the same chemical preparation method is used to first oxidize and polymerize isomelanin nanoparticles and then add the same mass of iron trichloride hexahydrate to obtain post-doped metal-naphthol nanoparticles as a control. The metal content loaded therein is tested and the results are as follows: Figure 7 As shown. The isomelanin nanomaterial provided by the present invention can achieve a higher metal loading. Figure 8 As shown, at 1A g -1 At a current rate of , the isomelanin nanomaterials prepared by first synthesizing the metal-naphthol complex also exhibited higher specific capacitance performance.
[0109] The technical solutions provided by the present invention are not limited to the above-mentioned embodiments. Any technical solutions formed by transformation and substitution using the structure and method of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing isomelanin nanomaterials, characterized in that The following steps are involved: S1 prepares a mixed solution of 1,8-dihydroxynaphthalene in acetone and water; S2 adds an aqueous solution of ferric chloride hexahydrate to the 1,8-dihydroxynaphthalene solution of S1 to form a 1,8-dihydroxynaphthalene-iron ion complex solution; S3: adding potassium dichromate aqueous solution to the complex solution prepared in S2, reacting and stirring to obtain a black solution; S4 centrifuges, washes, and dries the black solution obtained in S3 to obtain isomelanin nanomaterials; S5 treats the isomelanin nanomaterial of S4 at high temperature under an inert atmosphere to obtain the isomelanin nanomaterial; S6 grinds and blends the isomelanin nanomaterials of S5 with KOH, and performs high temperature treatment under an inert atmosphere to obtain a black mixed material; S7 washes the black mixed material of S6 with water, centrifuges, and dries to obtain isomelanin nanomaterials with a large specific surface area.
2. The method for preparing an isomelanin nanomaterial according to claim 1, characterized in that: In S1, the volume fraction of acetone in the mixed solvent is 5-25%, and the volume fraction of water is 75-95%; The content of 1,8-dihydroxynaphthalene in the 1,8-dihydroxynaphthalene solution is 0.5-3 mg / mL.
3. The method for preparing an isomelanin nanomaterial according to claim 1, characterized in that: In S2, the amount of the aqueous solution of ferric chloride hexahydrate added is based on a mass ratio of 1,8-dihydroxynaphthalene to ferric chloride hexahydrate of 1:0.5-1:
1.
4. The method for preparing an isomelanin nanomaterial according to claim 1, characterized in that: In S2, the amount of potassium dichromate solution added is based on a mass ratio of 1,8-dihydroxynaphthalene to potassium dichromate of 1:0.5-1:1; The stirring time is 4-48h.
5. The method for preparing an isomelanin nanomaterial according to claim 1, characterized in that: The specific step of S4 is to heat the isomelanin nanomaterial obtained in S3 to a heat treatment temperature of 500°C-1000°C at a heating rate of 2-10°C / min under an inert gas atmosphere, heat treat for 1-4 hours, and then return to room temperature at a cooling rate of 2-10°C / min to obtain the isomelanin nanomaterial.
6. The method for preparing an isomelanin nanomaterial according to claim 1, characterized in that: In S5, the mass ratio of the isomelanin nanomaterial obtained in S4 to KOH is 1:1-1:20; The specific steps of S5 are as follows: grinding and blending the isomelanin nanomaterial obtained in S4 with KOH, and then heating the temperature to 500°C-1000°C at a heating rate of 2-10°C / min under an inert gas atmosphere, performing heat treatment for 1-4 hours, and then cooling the temperature to room temperature at a cooling rate of 2-10°C / min to obtain a black mixed material.
7. An isomelanin nanomaterial prepared by the method according to any one of claims 1 to 5.
8. The isomelanin nanomaterial according to claim 7, wherein the specific surface area is greater than 1900 m 2 / g.
9. An electrode piece of isomelanin nanomaterial, characterized in that: The isomelanin nanomaterial is mixed with carbon black and polytetrafluoroethylene, ultrasonically dispersed in an aqueous solution and then dried, and the obtained black material is folded and rolled to obtain an isomelanin-based carbon nanofilm, which is then pressed with a current collector (at 0.5-50 MPa to obtain an isomelanin nanomaterial pole piece; The isomelanin nanomaterial is prepared by the method for preparing the isomelanin nanomaterial according to any one of claims 1 to 5.
10. The pole piece of isomelanin nanomaterial according to claim 9, characterized in that: The mass ratio of polytetrafluoroethylene to the large specific surface area iso-melanin-based carbon nanomaterial is 1:5-1:
20. Wherein, the mass ratio of polytetrafluoroethylene to carbon black is 1:0.2-1:5.
Citation Information
Patent Citations
Preparation method for synchronous-grown wafer-level AB-stack double-layer graphene and equipment for preparation method
CN106087051A
Microporous carbon and preparation method thereof
CN112427015A